2007
DOI: 10.1111/j.2006.0906-7590.04939.x
|View full text |Cite
|
Sign up to set email alerts
|

The ability to mount multiple immune responses simultaneously varies across the range of the tree swallow

Abstract: Variation in immune responses is an important part of life history variation. When correlations between multiple immune measures are reported, studies report different patterns. I tested whether the correlation between levels of immune response was consistent across a species range. The ability of tree swallows Tachycineta bicolor to simultaneously produce immune responses to both a humoral immune response and T-cell mediated local inflammation to PHA was tested at three sites that span the breeding range. Fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 52 publications
2
24
0
Order By: Relevance
“…This finding may indicate a trade-off between different immune branches suggesting that when one part of the immune system is challenged the other part is downregulated. Such a trade-off was found in Tree Swallows Tachycineta bicolor (Ardia 2007). Individuals that mounted a strong response against phytohaemagglutinin, which stimulates the cellular and innate component of the immune system, had reduced humoral antibody response against sheep red blood cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This finding may indicate a trade-off between different immune branches suggesting that when one part of the immune system is challenged the other part is downregulated. Such a trade-off was found in Tree Swallows Tachycineta bicolor (Ardia 2007). Individuals that mounted a strong response against phytohaemagglutinin, which stimulates the cellular and innate component of the immune system, had reduced humoral antibody response against sheep red blood cells.…”
Section: Discussionmentioning
confidence: 97%
“…Immune responses are extremely complex, reflecting the need to protect the host against a plethora of pathogens (Nelson et al 2002). Moreover, trade-offs between different immune branches can arise (Ardia 2007), and an increase in one measure may evoke a reduction in another. Second, the sampling period may be too short or sampling is too infrequent to describe seasonal changes in the physiological condition and immune activity effectively (e.g.…”
mentioning
confidence: 99%
“…The interpretation of relationships between immunological and ecological variables is complicated by the possibility that within‐year associations between immune markers can vary with year of observation (e.g. Ardia ; Hegemann et al . ; Pigeon et al .…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis remains largely untested in wild populations, particularly in reptiles. Few ecological studies have assessed the relations between humoral and cellular immune components (Blount et al 2003;Ardia 2007). An earlier study, involving the common lizard (Meylan et al 2010), found a negative correlation between humoral and cellular response.…”
Section: Physiological Adjustments During the Immune Responsementioning
confidence: 99%